Wild Plant Genetic Resources in North America: An Overview - Greene, Stephanie L.; Khoury, Colin K.; Williams, Karen A. (Springer, 2018)
North America, including Canada, Mexico, and the United States, is rich in plant species used by humans in both ancient and modern times. A select number of these have become globally important domesticated crops, including maize, beans, cotton, and sunflower. Many other native and also naturalized species have potential for use, either directly or as genetic resources for breeding agricultural crops. However, despite increasing recognition of their potential value, deficiencies in information, conservation, and access to the diversity in these plants hinder their further use. This chapter provides an overview of the agriculturally relevant wild plant resources of North America, with focus on wild relatives of globally important major crops, as well as the wild cousins of regionally and locally important domesticates. The chapter concludes by providing an overview of strategies for conserving wild plant genetic resources, including the international regulatory frameworks affecting policies to various degrees in Canada, Mexico, and the United States.